Understanding the SO2 Degassing Budget of Mt Etna's Paroxysms: First Clues From the December 2015 Sequence - D'Aleo, Roberto; Bitetto, Marcello; Delle Donne, Dario; Coltelli, Mauro; Coppola, Diego; McCormick Kilbride, Brendan; Pecora, Emilio; Ripepe, Maurizio; Salem, Lois Claire; Tamburello, Giancarlo; Aiuppa, Alessandro (Frontiers in Earth Science, 2019)
The persistent open-vent activity of basaltic volcanoes is periodically interrupted by spectacular but hazardous paroxysmal explosions. The rapid transition from quiescence to explosive eruption poses a significant challenge for volcanic hazard assessment and mitigation, and improving our understanding of the processes that trigger these paroxysmal events is critical. Although magmatic gas is unquestionably the driver, direct measurements of a paroxysm's gas flux budget have remained challenging, to date. A particularly violent paroxysmal sequence took place on Etna on December 2015, intermittently involving all summit craters, especially the Voragine (VOR) that had previously displayed no activity for several years. Here, we characterize the volcano's SO2 degassing budget prior to, during and after this paroxysmal sequence, using ground-based (UV-Camera) and satellite (OMI) observations, complemented with ground- and space-borne thermal measurements. We make use of the high spatial resolution of UV-cameras to resolve SO2 emissions from the erupting VOR crater for the first time, and to characterize temporal switches in degassing activity from VOR to the nearby New Southeast Crater (NSEC). Our data show that onset of paroxysmal activity on December 3–5 was marked by visible escalation in VOR SO2 fluxes (4,700–8,900 tons/day), in satellite-derived thermal emissions (2,000 MW vs. 2–11 MW in July-November 2015), and in OMI-derived daily SO2 masses (5.4 ± 0.7 to 10.0 ± 1.3 kilotonnes, kt; 0.5 kt was the average in the pre-eruptive period). Switch in volcanic activity from VOR to NSEC on December 6 was detected by increasing SO2 fluxes at the NSEC crater, and by decaying SO2 emissions at VOR, until activity termination on December 19. Taken together, our observations infer the total degassed SO2 mass for the entire VOR paroxysmal sequence at 21,000 ± 2,730 t, corresponding to complete degassing of 1.9 ± 0.3 Mm3 of magma, or significantly less than the measured erupted magma volumes (5.1–12 Mm3). From this mismatch we propose that only a small fraction of the erupted magma was actually emplaced in the shallow plumbing system during (or shortly prior) the paroxysmal sequence. Rather, the majority of the erupted magma was likely stored conduit magma, having gone through extensive degassing for days to weeks prior to the paroxysm.